2022
DOI: 10.3390/s22113975
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Based Intelligent Routing Protocol with Q-Learning for Mission-Critical Wireless Sensor Networks

Abstract: Mission-critical wireless sensor networks require a trustworthy and punctual routing protocol to ensure the worst-case end-to-end delay and reliability when transmitting mission-critical data collected by various sensors to gateways. In particular, the trustworthiness of mission-critical data must be guaranteed for decision-making and secure communications. However, it is a challenging issue to meet the requirement of both reliability and QoS in sensor networking environments where cyber-attacks may frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…To prioritize trustworthiness mainly for mission-critical WSNs, a Q-learning based routing protocol is proposed in Keum and Ko. 16 Its two main parameters are efficient energy management and detecting malicious nodes. Since static sinks causes sink hole issues, Krishnan and Lim 28 proposed a routing protocol for mobile sink based on Q-learning.…”
Section: Improves Uav Lifetime and Balances Energy Consumption Betwee...mentioning
confidence: 99%
See 3 more Smart Citations
“…To prioritize trustworthiness mainly for mission-critical WSNs, a Q-learning based routing protocol is proposed in Keum and Ko. 16 Its two main parameters are efficient energy management and detecting malicious nodes. Since static sinks causes sink hole issues, Krishnan and Lim 28 proposed a routing protocol for mobile sink based on Q-learning.…”
Section: Improves Uav Lifetime and Balances Energy Consumption Betwee...mentioning
confidence: 99%
“…In Kim et al, 15 Q‐learning is used to build a dynamic packet scheduling policy when the traffic condition changes dynamically and the data transmission pattern cannot be acquired. To prioritize trustworthiness mainly for mission‐critical WSNs, a Q‐learning based routing protocol is proposed in Keum and Ko 16 . Its two main parameters are efficient energy management and detecting malicious nodes.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep reinforcement learning (DRL) algorithms are successfully applied to complex high-dimensional problems, mainly due to the use of deep neural networks (DNN) for function approximations [1]. Researchers have applied DRL algorithms for various problems in mobile ad-hoc networks (MANETs), e.g., for minimizing average or worst-case end-to-end delay in routing problems [2], [3] and routing path optimization [4]. In [5], it is shown that the DRL-based DeepCQ+ algorithm outperforms the state-of-the-art robust routing for dynamic networks (R2DN) [6].…”
Section: Introductionmentioning
confidence: 99%